2016
DOI: 10.1007/s10443-016-9560-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mode I Interlaminar Fracture Toughness of Stitched Glass/Epoxy Composites

Abstract: This study examines the improvement of Interlaminar Fracture Toughness (IFT) of multilayered 3D glass/epoxy textile composites when through thickness reinforcement is introduced. Three stitching techniques have been examined: Modified Lockstitch (ISO-301), Single-yarn Orthogonal-stitch (ISO-205) and Double-yarn Orthogonal-stitch (ISO-205). It was found that the use of class ISO-205 manual-type stitched reinforcement significantly enhanced the Mode I-IFT, G IC measured using a Double Cantilever Beam technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The fracture mechanics showed energy dissipation through matrix deformation, fibre de-bonding, fibre breakage and fibre pull-out Furthermore, a high stress concentration around stitch fibres can also reduce the fracture toughness. This is because a higher amount stitched fibres can cause an in-plane fibre misalignment [17,19]. Figure 4.…”
Section: Mode-i Double Cantilever Beam Testingmentioning
confidence: 99%
“…The fracture mechanics showed energy dissipation through matrix deformation, fibre de-bonding, fibre breakage and fibre pull-out Furthermore, a high stress concentration around stitch fibres can also reduce the fracture toughness. This is because a higher amount stitched fibres can cause an in-plane fibre misalignment [17,19]. Figure 4.…”
Section: Mode-i Double Cantilever Beam Testingmentioning
confidence: 99%
“…To determine the mode I fracture toughness according to the ASTM D5528 standard, three methods are used [78]: the modified beam method (MBT) [163165], the compliance calibration (CC) method and the modified compliance calibration (MCC) method. The difference between them by means of fracture results is not more than 3.1%.…”
Section: Data Reduction Methodsmentioning
confidence: 99%
“…Some experimental studies have been conducted on stitched unidirectional or woven FRPC composites to find interlaminar delamination. It was found that the stitched FRPC laminates present significantly larger interlaminar toughness as compared to un-stitched laminates [4,7479], and that an increase in stitch density caused an increase in mode I strain energy release rate [4,74–76]. A recent study [80] has been carried out on flax fiber-epoxy composite laminates to find the effect of stitching in-through-thickness direction on mode I fracture toughness.…”
Section: Types Of Preform Used In Textile-reinforced Polymer Compositmentioning
confidence: 99%
“…There are several manufacturing techniques available for making reinforcement preforms for composite laminates and these include (1) Braiding [80,81], (2) Stitching [82][83][84][85][86][87][88], (3) 3D Z-Pinning [89][90][91], and (4) 3D weaving [92]. The schematic of different types of 3D sandwich structure is depicted in Figure 5.…”
Section: D Sandwich Structuresmentioning
confidence: 99%
“…Braiding, which requires a complicated manufacturing process, may involve the loss of flexibility in laminate construction. ILFT can be substantially increased by adding the reinforcement in the thickness direction like non crimp fabrics with stitches, z-pinning, and metallic wire usage as well as 3-D structural composites [2,4,32,83,84,[93][94][95][96][97]. It was reported [4] that extensive crack branching caused toughening in the textile composites as the interlaminar crack followed a meandrous crack path inside a complex fiber architecture.…”
Section: D Sandwich Structuresmentioning
confidence: 99%